A bibliometric analysis of optic atrophy from 2003 to 2023: research trends and hot spots - Liyuan Wang; Liyuan Wang; Liyuan Wang; Tianyang Yu; Tianyang Yu; Runze Wang; Lijuan Fu; Lijuan Fu; Feixue Dong; Feixue Dong; Shuang Zhao; Shuang Zhao; et al. (Frontiers in Medicine)
BackgroundOptic atrophy (OA) is primarily caused by damage to the retinal pathway system, including widespread degeneration of retinal ganglion cells and axons, leading to visual impairment and blindness. Despite its clinical significance and diverse etiological factors, there is currently a lack of comprehensive bibliometric analyses exploring research trends and hotspots within this field.MethodThis study retrieved relevant literature on OA published between 2003 and 2023 from the Web of Science Core Collection database. We conducted a bibliometric analysis using tools such as CiteSpace, VOSviewer, and SCImago Graphica to examine annual publication trends, co-occurrence patterns, collaborative networks among countries and institutions, and the evolution of research hotspots of OA.ResultsA total of 5,274 publications were included in the bibliometric analysis, comprising 4,561 research articles and 713 review articles. The United States emerged as the leading country in OA research, followed by Germany and China. Over the past two decades, the primary research hotspots focused on “mitochondrial dysfunction,” “hereditary optic neuropathy,” “ocular hypertension” and “diagnostic techniques.” Future research trends are likely to revolve around “molecular mechanisms” and “therapeutic targets.”ConclusionThis bibliometric analysis provides an overview of research developments in OA over the past 20 years, highlighting the emphasis on the pathological basis of OA and advancements in diagnostic and therapeutic approaches. Future studies should continue to explore the molecular basis of mitochondrial dysfunction to identify potential gene therapy targets for treating OA.